Notes on the Pontederiaceae names described in Vellozo'sFlora fluminensis - Marco Octávio de Oliveira Pellegrini (Rodriguésia)
AbstractNotes on the Pontederiaceae names described in Vellozo's Flora fluminensisThe names of Pontederiaceae described by Vellozo in his Flora fluminensis are here revised, with an orthographical correction, two lectotypes and one epitype designated.